2004
DOI: 10.1177/0193945903259579
|View full text |Cite
|
Sign up to set email alerts
|

Hispanic Adolescent Farmworkers’ Perceptions Associated with Pesticide Exposure1

Abstract: The migrant farmworker population in the United States is a vulnerable and understudied population whose characteristics are constantly shifting. The number of youth involved in agriculture work is increasing, and they, in particular, may be at increased risk for occupational hazards, such as pesticide exposure. The present study utilized an ecological framework for focus group discussions with 33 adolescent migrant farmworkers in Oregon. Adolescents' risk perception and health beliefs associated with pesticid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 25 publications
(17 reference statements)
3
64
0
2
Order By: Relevance
“…Other known behavioral factors linked with exposure to pesticides and agricultural chemicals include the storage of these chemicals in containers other than the original labeled container and cross contamination due to not laundering field clothes separately [13][14][15]. This analysis found that over half of the pesticide-and agricultural chemical-related events were due to human error and could have resulted from these behavioral factors.…”
Section: Discussionmentioning
confidence: 99%
“…Other known behavioral factors linked with exposure to pesticides and agricultural chemicals include the storage of these chemicals in containers other than the original labeled container and cross contamination due to not laundering field clothes separately [13][14][15]. This analysis found that over half of the pesticide-and agricultural chemical-related events were due to human error and could have resulted from these behavioral factors.…”
Section: Discussionmentioning
confidence: 99%
“…Se ha demostrado que en muchos casos la mezcla de dos plaguicidas del mismo o distinto grupo provoca mayor efecto en plagas y enfermedades, resultado de la suma de las acciones individuales de cada uno de ellos por separado. Este mecanismo llega a destruir no sólo a los insectos nocivos, sino también a los benéficos, por la aplicación de un tratamiento intenso (Garaj & Zeljezic, 2001;Salazar, Napolitano, Scherer & McCauley, 2004). El uso de mezclas de plaguicidas también fue reportado por Gómez et al (2000) y Martínez et al (2009), que se aplicaron en invernaderos en el estado de Morelos y en campos agrícolas del norte de Sinaloa.…”
Section: Discussionunclassified
“…Although not referred to as an analytic framework per se, the theory of neighborhoods affecting health was explored in seven articles (Bowie et al 2005;Israel et al 2006;Michael et al 2006;Schaefer-McDaniel 2007;Songsore and McGranahan 1998;Timmermans 2007;Warr et al 2007). Other theoretical perspectives referred to in the analyses include ecological theory (Salazar et al 2004;Schaefer-McDaniel 2007) and social constructionism (Moffatt and PlessMulloli 2003;Shriver 2001;Shriver et al 1998). Two articles referred to the environmental stress and coping literature as an analytic framework (Haines et al 2003;Wakefield et al 2001).…”
Section: Theoretical Framework and Analysesmentioning
confidence: 99%